Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pmed.1003680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sunflower seed oil emollient therapy on newborn infant survival in Uttar Pradesh, India: A community-based, cluster randomized, open-label controlled trial

Abstract: Background Hospitalized preterm infants with compromised skin barrier function treated topically with sunflower seed oil (SSO) have shown reductions in sepsis and neonatal mortality rate (NMR). Mustard oil and products commonly used in high-mortality settings may possibly harm skin barrier integrity and enhance risk of infection and mortality in newborn infants. We hypothesized that SSO therapy may reduce NMR in such settings. Methods and findings This was a population-based, cluster randomized, controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…We found that intervention with SSO therapy significantly improved the growth of newborn infants compared with usual practices by ∼1 g · kg −1 · d −1 , which is below that reported previously ( 31 , 35 , 37 , 39 , 42 , 44–54 ) and summarized in meta-analyses (1.1–2.9 g · kg −1 · d −1 ) ( 37 , 39 , 53 , 54 ) for hospitalized, very-preterm infants under efficacy conditions. Although acceptance of SSO (i.e., any use) was high in intervention infants (89%) ( 41 ), because adherence to exclusive use of SSO was low in our study—increasing by 65% from 22.6% (first quartile) to 37.2% (fourth quartile) of infants in the intervention group—per-protocol analysis was important. Per-protocol analysis revealed that infants in the intervention group who were exclusively treated with SSO as intended showed a 1.3-g · kg −1 · d −1 greater growth velocity than infants in the comparison group who exclusively received mustard oil massage.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…We found that intervention with SSO therapy significantly improved the growth of newborn infants compared with usual practices by ∼1 g · kg −1 · d −1 , which is below that reported previously ( 31 , 35 , 37 , 39 , 42 , 44–54 ) and summarized in meta-analyses (1.1–2.9 g · kg −1 · d −1 ) ( 37 , 39 , 53 , 54 ) for hospitalized, very-preterm infants under efficacy conditions. Although acceptance of SSO (i.e., any use) was high in intervention infants (89%) ( 41 ), because adherence to exclusive use of SSO was low in our study—increasing by 65% from 22.6% (first quartile) to 37.2% (fourth quartile) of infants in the intervention group—per-protocol analysis was important. Per-protocol analysis revealed that infants in the intervention group who were exclusively treated with SSO as intended showed a 1.3-g · kg −1 · d −1 greater growth velocity than infants in the comparison group who exclusively received mustard oil massage.…”
Section: Discussionmentioning
confidence: 61%
“…Previously we examined the impacts of gentle massage with SSO compared with usual skin care practices in a population-based cohort of newborn infants in a rural community in Uttar Pradesh, India. We showed no overall effect on neonatal mortality but a significant 52% reduction in mortality among the subgroup of very-low-birth-weight (VLBW) infants ≤1500 g ( 41 ). Here we examine the effects of SSO treatment on the neonatal growth and morbidity of the infants in that trial.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations